All-solid-state battery and method for producing same
A full-solid battery with a laminated structure using a coated solid electrolyte layer addresses the safety and conductivity issues of lithium-ion batteries, enhancing stability and longevity by preventing dendrite growth and reducing resistance.
Patent Information
- Application Number
- JP2020213610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-12-23
AI Technical Summary
Lithium-ion batteries using organic solvents are flammable and have low ionic conductivity, posing safety risks and limiting their application in high-capacity and large-sized batteries, while solid electrolytes with high ionic conductivity face challenges in suppressing metal dendrite growth leading to short circuits.
A full-solid battery structure is developed with a laminated design where the surface of first particles in the solid electrolyte layer is coated with a second material having lower ionic conductivity, formed through a dry mixing process to hinder ion conduction and prevent dendrite growth.
The structure effectively suppresses short circuits and enhances battery life by detouring dendrite growth, maintaining stable ionic conduction and reducing resistance components.
Smart Images

Figure 0007624605000002 
Figure 0007624605000003 
Figure 0007624605000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an all-solid-state battery and a manufacturing method thereof, and in particular to an all-solid-state battery using a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and a manufacturing method thereof. [Background technology]
[0002] In recent years, the development of rechargeable secondary batteries has been required due to the trend toward lighter and more cordless electronic devices such as personal computers and mobile phones. Secondary batteries include nickel-cadmium batteries, nickel-metal hydride batteries, lead-acid batteries, and lithium-ion batteries. Among these, lithium-ion batteries have attracted attention due to their characteristics of light weight, high voltage, and high energy density.
[0003] In the field of automobiles, such as electric vehicles and hybrid vehicles, importance is being placed on the development of secondary batteries with high battery capacity, and the demand for lithium-ion batteries is showing an increasing trend.
[0004] A lithium-ion battery is composed of a positive electrode layer, a negative electrode layer, and an electrolyte disposed between them. The electrolyte is, for example, an electrolytic solution in which a supporting salt such as lithium hexafluorophosphate is dissolved in an organic solvent, or a solid electrolyte. Currently, lithium-ion batteries that are widely used are flammable because they use an electrolytic solution containing an organic solvent. Therefore, materials, structures, and systems are required to ensure the safety of lithium-ion batteries. In contrast, it is expected that the above-mentioned materials, structures, and systems can be simplified by using a non-flammable solid electrolyte as the electrolyte, and it is thought that it is possible to increase the energy density, reduce the manufacturing cost, and improve the productivity. Hereinafter, batteries using solid electrolytes such as lithium-ion batteries using solid electrolytes will be referred to as "all-solid-state batteries."
[0005] Solid electrolytes can be broadly divided into organic solid electrolytes and inorganic solid electrolytes. Organic solid electrolytes have an ionic conductivity of 10 -6The ionic conductivity of the electrolyte is about 10 -3 Compared to the ionic conductivity of about 10 S / cm, the ionic conductivity is extremely low. Therefore, it is difficult to operate an all-solid-state battery using an organic solid electrolyte in an environment of 25°C. Oxide-based solid electrolytes, sulfide-based solid electrolytes, and halide-based solid electrolytes are common inorganic solid electrolytes. The ionic conductivity of these is around 10 -4 ~10 -3 S / cm, which is a relatively high ionic conductivity. Therefore, in the development of all-solid-state batteries aimed at larger sizes and higher capacities, research into all-solid-state batteries that can be made larger using sulfide-based solid electrolytes has been actively conducted in recent years.
[0006] For example, Patent Document 1 discloses a method for forming a solid electrolyte layer with a high filling rate in which voids between solid electrolyte particles that constitute the solid electrolyte layer of an all-solid-state battery are filled. In the method described in Patent Document 1, electrolyte particles with two different particle sizes, large and small, are used as the electrolyte particles that constitute the solid electrolyte layer, so that the small particles fill the voids between the large particles. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2013-157084 A Summary of the Invention [Problem to be solved by the invention]
[0008] In general, in all-solid-state batteries, metallic lithium (Li) precipitates on the surface of the negative electrode active material constituting the negative electrode layer as the battery is repeatedly charged and discharged, and the metallic Li gradually grows along the particle surfaces of the particles of the solid electrolyte material constituting the solid electrolyte layer and along the interfaces between the particles. As a result, the grown metallic Li causes electrical conduction between the positive electrode layer and the negative electrode layer, resulting in a short circuit. Hereinafter, the grown metallic Li and other metals may be referred to as "dendrites."
[0009] In view of this, the present disclosure provides an all-solid-state battery and the like that can suppress the occurrence of short circuits due to repeated charging and discharging of the battery. [Means for solving the problem]
[0010] An all-solid-state battery according to one embodiment of the present disclosure has a structure in which a positive electrode current collector, a positive electrode layer including a positive electrode active material and a first solid electrolyte, a solid electrolyte layer including a third solid electrolyte, a negative electrode layer including a negative electrode active material and a second solid electrolyte, and a negative electrode current collector are laminated in this order, the third solid electrolyte being composed of a first material and a second material having an ionic conductivity lower than that of the first material, the first material being composed of first particles, and at least a portion of the surface of the first particles being coated with the second material.
[0011] A method for producing an all-solid-state battery according to an embodiment of the present disclosure includes, in the method for producing an all-solid-state battery, a stirring and kneading step of forming the third solid electrolyte by dry kneading the first material and the second material by applying a pressure force and a shear force before forming the solid electrolyte layer. Effect of the Invention
[0012] The all-solid-state battery etc. according to the present disclosure can suppress the occurrence of short circuits caused by repeated charging and discharging of the battery. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of an all-solid-state battery according to an embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view for explaining a method for manufacturing an all-solid-state battery according to an embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing the mixing behavior of the first particle and the second particle in the embodiment. [Figure 4] FIG. 4 is a schematic diagram showing a cross section of the evaluation sample used in Comparative Example 1 and Example 1. As shown in FIG. [Diagram 5] FIG. 5 is a schematic diagram for explaining the state of dendrite generation in the evaluation sample in Comparative Example 1. As shown in FIG. [Figure 6] FIG. 6 is a schematic diagram for explaining the state of dendrite generation in the evaluation sample in Example 1. As shown in FIG. [Figure 7A] FIG. 7A is a perspective view that illustrates a state in which second particles cover first particles in the embodiment. [Figure 7B] FIG. 7B is a cross-sectional view of the first particle and the second particle shown in FIG. 7A taken along plane VIIb. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An all-solid-state battery according to one embodiment of the present disclosure has a structure in which a positive electrode current collector, a positive electrode layer including a positive electrode active material and a first solid electrolyte, a solid electrolyte layer including a third solid electrolyte, a negative electrode layer including a negative electrode active material and a second solid electrolyte, and a negative electrode current collector are laminated in this order, the third solid electrolyte being composed of a first material and a second material having an ionic conductivity lower than that of the first material, the first material being composed of first particles, and at least a portion of the surface of the first particles being coated with the second material.
[0015] As a result, during charging and discharging of the all-solid-state battery, the second material covering the first particles prevents the conduction of ions such as Li ions moving within the first particles, causing the growth (dendrites) of metals such as metallic Li in the solid electrolyte layer to multiply branch. As a result, it becomes difficult for dendrites extending from the positive electrode layer to reach the negative electrode layer. Therefore, the all-solid-state battery according to this embodiment can suppress the occurrence of a short circuit. Furthermore, in the all-solid-state battery according to this embodiment, the time until a short circuit occurs is extended, thereby improving the battery life.
[0016] Furthermore, for example, a coverage rate of the surface of the first particle with the second material may be 5% or more and 62% or less.
[0017] This makes it possible to suppress an increase in the resistance component in the ion conduction of the solid electrolyte layer, thereby suppressing a deterioration in the battery characteristics and obtaining a short circuit suppression effect.
[0018] Also, for example, the second material may be composed of second particles having an average particle size smaller than that of the first particles.
[0019] This makes it possible to easily obtain first particles that are partially coated with the second material, and also makes it easy to control the mixing ratio of the first material and the second material, thereby achieving stable battery performance.
[0020] Furthermore, for example, the ratio of the average particle diameter of the second particles to the average particle diameter of the first particles may be 1% or more and 20% or less.
[0021] This makes it easier for the surfaces of the first particles to be coated with the second material composed of the second particles, making it easier to form a coating structure of the second material, thereby reducing the complexity of manufacturing the all-solid-state battery and enabling it to be manufactured stably.
[0022] Furthermore, for example, in a coating structure of the second material that coats the first particles, the coating length may be 10 times or more larger than the coating thickness.
[0023] This makes it possible to obtain a short circuit suppression effect while suppressing an increase in the resistance component in ion conduction in the thickness direction of the coating structure made of the second material.
[0024] Furthermore, for example, a volume ratio of the second material to a total volume of the first material and the second material may be 5% or more and 50% or less.
[0025] This makes it possible to obtain a short circuit suppression effect while suppressing an increase in the resistance component in the ion conduction of the solid electrolyte layer.
[0026] Furthermore, for example, in a cross-sectional view of the solid electrolyte layer, the variation in the volume ratio of the second material to the total volume of the first material and the second material in the thickness direction of the solid electrolyte layer may be 10% or less.
[0027] This makes it difficult for bias in ion conduction to occur within the solid electrolyte layer, and stable battery charge / discharge characteristics can be obtained even when the charge / discharge rate is high.
[0028] Also, for example, the oxygen content of the second material may be higher than the oxygen content of the first material.
[0029] In this way, by increasing the oxygen content of the second material, for example by oxidizing the solid electrolyte material, the ionic conductivity of the second material tends to decrease, so that a second material having a lower ionic conductivity than the first material can be easily prepared.
[0030] Furthermore, for example, the ratio of the ionic conductivity of the second material to the ionic conductivity of the first material may be 0.2% or more and 10% or less.
[0031] This makes it possible to obtain a short circuit suppression effect while suppressing an increase in the resistance component in the ion conduction of the solid electrolyte layer.
[0032] In addition, a method for producing an all-solid-state battery according to an embodiment of the present disclosure includes, in the method for producing an all-solid-state battery described above, a stirring and kneading step of forming the third solid electrolyte by dry kneading the first material and the second material while applying a pressure force and a shear force before forming the solid electrolyte layer.
[0033] As a result, by kneading the first material and the second material before forming the solid electrolyte layer, a structure in which the surfaces of the first particles are coated with the second material is formed, and such a coating structure is stabilized, so that an all-solid-state battery with an improved short circuit suppression effect can be manufactured.
[0034] Furthermore, for example, the production method may further include a crushing step of crushing the first material in the presence of oxygen to form the second material, prior to the stirring and kneading step.
[0035] By exposing the first material to an oxygen atmosphere, the ionic conductivity of the first material can be reduced and the resulting material can be used as the second material, making it possible to manufacture the first and second materials from the same material, and therefore the second material can be easily prepared.
[0036] The all-solid-state battery in the embodiment will be described in detail below. Note that the embodiments described below are all comprehensive or specific examples. The numerical values, shapes, materials, components, arrangement positions and connection forms of the components, and processes shown in the following embodiments are examples and are not intended to limit the present disclosure.
[0037] Furthermore, in this specification, terms indicating the relationship between elements, such as "parallel," terms indicating the shape of an element, such as "rectangle," and numerical ranges are not expressions that only express a strict meaning, but are expressions that include a substantially equivalent range, for example, a difference of about a few percent.
[0038] In addition, each figure is a schematic diagram in which emphasis, omission, or adjustment of the ratio is appropriately performed in order to illustrate the present disclosure, and is not necessarily precisely illustrated, and may differ from the actual shape, positional relationship, and ratio. In each figure, the same reference numerals are given to substantially the same configurations, and duplicated explanations may be omitted or simplified.
[0039] In this specification, the terms "upper" and "lower" in the configuration of an all-solid-state battery do not refer to the upper direction (vertically upward) and lower direction (vertically downward) in absolute spatial recognition, but are used as terms defined by a relative positional relationship based on the stacking order in the stacking configuration. In addition, the terms "upper" and "lower" are applied not only to the case where two components are arranged in close contact with each other and are in contact with each other, but also to the case where two components are arranged with a gap between them and another component is present between the two components.
[0040] In this specification, a cross-sectional view is a view showing a cross-section of the central portion of an all-solid-state battery cut in the stacking direction.
[0041] (Embodiment) <Configuration> [A. All-solid-state battery] The outline of the all-solid-state battery in this embodiment will be described with reference to FIG. 1. FIG. 1 is a schematic diagram showing a cross section of an all-solid-state battery 100 in this embodiment. The all-solid-state battery 100 in this embodiment includes a positive electrode current collector 6, a negative electrode current collector 7, a positive electrode layer 20 formed on a surface of the positive electrode current collector 6 close to the negative electrode current collector 7 and containing a positive electrode active material 3 and a solid electrolyte 1, a negative electrode layer 30 formed on a surface of the negative electrode current collector 7 close to the positive electrode current collector 6 and containing a negative electrode active material 4 and a solid electrolyte 5, and a solid electrolyte layer 10 disposed between the positive electrode layer 20 and the negative electrode layer 30 and containing a solid electrolyte 2 having at least ion conductivity. In other words, the all-solid-state battery 100 has a structure in which the positive electrode current collector 6, the positive electrode layer 20, the solid electrolyte layer 10, the negative electrode layer 30, and the negative electrode current collector 7 are stacked in this order. In the present embodiment, solid electrolyte 1 is an example of a first solid electrolyte, solid electrolyte 5 is an example of a second solid electrolyte, and solid electrolyte 2 is an example of a third solid electrolyte.
[0042] In the present embodiment, the solid electrolyte 2 included in the solid electrolyte layer 10 is composed of a mixture of at least two types of solid electrolytes having different ionic conductivities, specifically, composed of a first material 21 made of a solid electrolyte material and a second material 22 made of a solid electrolyte material having a lower ionic conductance than the first material 21. The first material 21 is composed of a collection of particles of the solid electrolyte material. The second material 22 is also composed of a collection of particles of the solid electrolyte material, but FIG. 1 shows a state of a film formed by the particles of the second material 22 (i.e., second particles described later) being densely packed. Therefore, in FIG. 1, the shape of the particles of the second material 22 is not shown. At least a part of the surface of the particles of the first material 21 (i.e., first particles described later) is in contact with the second material 22 and is covered by the second material 22. The second material 22 may be composed of a solid electrolyte material having a layered or film-like shape.
[0043] The all-solid-state battery 100 is formed, for example, by the following method. First, a positive electrode layer 20 containing a positive electrode active material 3 formed on a positive electrode current collector 6 made of a metal foil, a negative electrode layer 30 containing a negative electrode active material 4 formed on a negative electrode current collector 7 made of a metal foil, and a solid electrolyte layer 10 containing a solid electrolyte 2 having ion conductivity and arranged between the positive electrode layer 20 and the negative electrode layer 30 are formed. Then, the positive electrode current collector 6 and the negative electrode current collector 7 are pressed from the outside at a pressure of, for example, 100 MPa or more and 1000 MPa or less, and the filling rate of at least one layer of each layer is set to 60% or more and less than 100%, thereby obtaining an all-solid-state battery 100. By setting the filling rate to 60% or more, the number of voids is reduced in the solid electrolyte layer 10, the positive electrode layer 20, or the negative electrode layer 30, so that lithium (Li) ion conduction and electron conduction are abundant, and good charge and discharge characteristics are obtained. The filling rate is the ratio of the volume occupied by the material excluding the voids between the materials to the total volume in each layer.
[0044] The pressed all-solid-state battery 100 is, for example, attached with terminals and housed in a case. As the case for the all-solid-state battery 100, for example, an aluminum laminate bag, a case made of metal such as stainless steel (SUS), iron or aluminum, or a case made of resin, etc., is used.
[0045] The solid electrolyte layer 10, the positive electrode layer 20, and the negative electrode layer 30 of the all-solid-state battery 100 in this embodiment will be described below.
[0046] [B. Solid electrolyte layer] First, a description will be given of the solid electrolyte layer 10. The solid electrolyte layer 10 in the present embodiment contains a solid electrolyte 2, and may further contain a binder.
[0047] [B-1. Solid electrolyte] The solid electrolyte 2 in this embodiment will be described. The solid electrolyte 2 is composed of at least a first material 21 made of a solid electrolyte material with high ion conductivity, and a second material 22 made of a solid electrolyte material with low ion conductivity. The ion conductivity of the second material 22 is lower than that of the first material 21. The characteristics relating to the shapes of the first material 21 and the second material 22 will be described in detail later.
[0048] The solid electrolyte material used for the first material 21 and the second material 22 constituting the solid electrolyte 2 includes sulfide-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes, which are general known materials. As the solid electrolyte material, any of sulfide-based solid electrolytes, halide-based solid electrolytes, and oxide-based solid electrolytes may be used. The type of sulfide-based solid electrolyte in the present embodiment is not particularly limited. Examples of the sulfide-based solid electrolyte include Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, and Li2S-P2S5. In particular, from the viewpoint of excellent ion conductivity of lithium, the sulfide-based solid electrolyte may contain Li, P, and S. In addition, the sulfide-based solid electrolyte may contain P2S5 because it has high reactivity with the binder and high binding property with the binder. The above description of "Li2S-P2S5" means a sulfide-based solid electrolyte made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0049] In this embodiment, the sulfide-based solid electrolyte is, for example, a sulfide-based glass ceramic containing Li2S and P2S5, and the ratio of Li2S and P2S5 may be within a range of 70:30 to 80:20, or may be within a range of 75:25 to 80:20, in terms of moles. By setting the ratio of Li2S and P2S5 within this range, a crystal structure with high ion conductivity can be obtained while maintaining the Li concentration that affects the battery characteristics. In addition, by setting the ratio of Li2S and P2S5 within this range, the amount of P2S5 that reacts with and bonds with the binder is easily secured.
[0050] As described above, the solid electrolyte 2 is composed of the first material 21 and the second material 22, which are at least two types of solid electrolyte materials having different ionic conductivities.
[0051] At least a portion of the surface of the particles of the solid electrolyte material constituting the first material 21 (i.e., the first particles described below) is covered with the second material 22. For example, the second material 22 partially covers the surface of the particles of the first material 21. Note that a portion of the second material 22 does not have to cover the surface of the particles of the first material 21. Furthermore, the solid electrolyte 2 may contain a solid electrolyte material other than the first material 21 and the second material 22.
[0052] [B-2. Binder] The binder in this embodiment will be described. The binder is an adhesive that does not have ionic conductivity or electronic conductivity and serves to bond materials in the solid electrolyte layer 10 together and the solid electrolyte layer 10 to other layers. A known binder for batteries is used as the binder. The binder in this embodiment may also include a thermoplastic elastomer to which a functional group that improves adhesion strength has been introduced. The functional group may also be a carbonyl group. From the viewpoint of improving adhesion strength, the carbonyl group may also be maleic anhydride. The oxygen atoms of the maleic anhydride of the binder react with the solid electrolyte 2 to bond the solid electrolytes 2 together via the binder, creating a structure in which the binder is arranged between the solid electrolytes 2, and as a result, the adhesion strength is improved.
[0053] As the thermoplastic elastomer, for example, styrene-butadiene-styrene (SBS), styrene-ethylene-butadiene-styrene (SEBS), etc. are used. This is because they have high adhesion strength and are highly durable in terms of the cycle characteristics of the battery. As the thermoplastic elastomer, a hydrogenated thermoplastic elastomer may be used. By using a hydrogenated thermoplastic elastomer, the reactivity and binding property are improved, and the solubility in the solvent used when forming the solid electrolyte layer 10 is improved.
[0054] The amount of binder added is, for example, 0.01% by mass or more and 5% by mass or less, and may be 0.1% by mass or more and 3% by mass or less, or 0.1% by mass or more and 1% by mass or less. By making the amount of binder added 0.01% by mass or more, binding via the binder is likely to occur, and sufficient adhesion strength is likely to be obtained. In addition, by making the amount of binder added 5% by mass or less, deterioration of battery characteristics such as charge / discharge characteristics is unlikely to occur, and further, even if physical properties such as hardness, tensile strength, and tensile elongation of the binder change, for example, in a low temperature region, charge / discharge characteristics are unlikely to deteriorate.
[0055] [C. Positive electrode layer] Next, the positive electrode layer 20 in this embodiment will be described. The positive electrode layer 20 in this embodiment includes a solid electrolyte 1 and a positive electrode active material 3. The positive electrode layer 20 may further include a conductive assistant such as acetylene black and Ketjen Black (registered trademark) for ensuring electronic conductivity, and a binder, if necessary. However, if the amount added is large, it will affect the battery performance, so it is desirable to add a small amount that does not affect the battery performance. The weight ratio of the solid electrolyte 1 to the positive electrode active material 3 is, for example, in the range of 50:50 to 5:95 (solid electrolyte 1:positive electrode active material 3), and may be in the range of 30:70 to 10:90. In addition, the volume ratio of the positive electrode active material 3 to the total volume of the positive electrode active material 3 and the solid electrolyte 1 is, for example, 60% or more and 80% or less. This volume ratio makes it easy to ensure both the lithium ion conduction path and the electron conduction path in the positive electrode layer 20.
[0056] The positive electrode current collector 6 is made of, for example, a metal foil such as SUS, aluminum, nickel, titanium, or copper.
[0057] [C-1. Solid electrolyte] The solid electrolyte 1 is at least one selected from the solid electrolyte materials listed in the above [B-1 solid electrolyte], and is not particularly limited. For example, the same solid electrolyte material as the first material 21 is used for the solid electrolyte 1.
[0058] [C-2. Binder] Since this is the same as the binder described above, the explanation will be omitted.
[0059] [C-3. Positive electrode active material] The positive electrode active material 3 in this embodiment will be described. For example, a lithium-containing transition metal oxide is used as the material for the positive electrode active material 3 in this embodiment. Examples of the lithium-containing transition metal oxide include LiCoO2, LiNiO2, LiMn2O4, LiCoPO4, LiNiPO4, LiFePO4, and LiMnPO4, as well as compounds obtained by substituting one or two different elements for the transition metals in these compounds. Examples of compounds obtained by substituting one or two different elements for the transition metals in the above compounds include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.5 Mn 1.5 Known materials such as O2 are used. The material for the positive electrode active material 3 may be used alone or in combination of two or more.
[0060] The positive electrode active material 3 is composed of, for example, a collection of particles. The particles of the positive electrode active material 3 are granulated particles in which a plurality of primary particles made of the above-mentioned material are aggregated, and in this specification, these granulated particles are referred to as the particles of the positive electrode active material 3. The average particle diameter of the positive electrode active material 3 is not particularly limited, but is, for example, 1 μm or more and 10 μm or less.
[0061] [D. Negative electrode layer] Next, the negative electrode layer 30 in this embodiment will be described. The negative electrode layer 30 in this embodiment includes a solid electrolyte 5 and a negative electrode active material 4. The negative electrode layer 30 may further include a conductive assistant such as acetylene black and ketjen black and a binder to ensure electronic conductivity, if necessary. However, if the amount of addition is large, it will affect the battery performance, so it is desirable to add a small amount that does not affect the battery performance. The ratio of the solid electrolyte 5 to the negative electrode active material 4 is, for example, in the range of 5:95 to 60:40, or may be in the range of 30:70 to 50:50, in terms of weight. In addition, the volume ratio of the negative electrode active material 4 to the total volume of the negative electrode active material 4 and the solid electrolyte 5 is, for example, 60% or more and 80% or less. This volume ratio makes it easy to ensure both the lithium ion conduction path and the electron conduction path in the negative electrode layer 30.
[0062] The negative electrode current collector 7 is made of, for example, a metal foil, such as SUS, copper, or nickel.
[0063] [D-1. Solid electrolyte] The solid electrolyte 5 is at least one selected from the solid electrolyte materials listed in [B-1. Solid Electrolyte] above, and is not particularly limited. For example, the same solid electrolyte material as the first material 21 is used for the solid electrolyte 5.
[0064] [D-2. Binder] Since this is the same as the binder described above, the explanation will be omitted.
[0065] [D-3. Negative electrode active material] The negative electrode active material 4 in this embodiment will be described. Examples of the material for the negative electrode active material 4 in this embodiment include metals that easily alloy with lithium, such as indium, tin, and silicon, carbon materials such as hard carbon and graphite, lithium, and Li4Ti5O 12 , SiO x Known materials such as the above are used.
[0066] The negative electrode active material 4 is composed of, for example, a collection of particles. The average particle size of the negative electrode active material 4 is not particularly limited, but is, for example, 1 μm or more and 15 μm or less.
[0067] <Manufacturing method> Next, a method for manufacturing the all-solid-state battery 100 in this embodiment will be described with reference to Fig. 2. Specifically, a method for manufacturing the all-solid-state battery 100 including the solid electrolyte layer 10, the positive electrode layer 20, and the negative electrode layer 30 will be described. Fig. 2 is a schematic cross-sectional view for explaining the method for manufacturing the all-solid-state battery 100.
[0068] The manufacturing method of the all-solid-state battery 100 includes, for example, a positive electrode layer forming step, a negative electrode layer forming step, a solid electrolyte layer forming step, a lamination step, and a pressing step. In the positive electrode layer forming step ((a) of FIG. 2), the positive electrode layer 20 is formed on the positive electrode current collector 6. In the negative electrode layer forming step ((b) of FIG. 2), the negative electrode layer 30 is formed on the negative electrode current collector 7. In the solid electrolyte layer forming step ((c) and (d) of FIG. 2), the solid electrolyte layer 10 is formed. In the lamination step and pressing step ((e) and (f) of FIG. 2), the positive electrode layer 20 formed on the positive electrode current collector 6, the negative electrode layer 30 formed on the negative electrode current collector 7, and the formed solid electrolyte layer 10 are laminated together so that the solid electrolyte layer 10 is disposed between the positive electrode layer 20 and the negative electrode layer 30, and pressed from the outside of the positive electrode current collector 6 and the negative electrode current collector 7. Also, The manufacturing method of the all-solid-state battery 100 includes, for example, a stirring and kneading step of kneading the first material 21 and the second material 22 in a dry state by applying a pressure force and a shear force before forming the solid electrolyte layer 10, thereby forming the solid electrolyte 2. Each step will be described in detail below.
[0069] [E. Positive electrode layer deposition process] As a film forming step of the positive electrode layer 20 (positive electrode layer forming step) in the present embodiment, for example, the following two methods, method (1) and method (2), can be mentioned.
[0070] (1) The positive electrode layer 20 in the present embodiment can be produced by a film-forming process including, for example, a coating process in which a positive electrode active material 3 and a solid electrolyte 1 are dispersed in an organic solvent, and a binder and a conductive assistant (not shown) are further dispersed in the organic solvent as necessary to produce a slurried positive electrode mixture, and the resulting positive electrode mixture is coated on the surface of the positive electrode current collector 6, a drying and firing process in which the resulting coating is heated and dried to remove the organic solvent, and a coating press process in which the dried coating formed on the positive electrode current collector 6 is pressed.
[0071] The method for applying the slurry is not particularly limited, but examples thereof include known application methods such as a blade coater, a gravure coater, a dip coater, a reverse coater, a roll knife coater, a wire bar coater, a slot die coater, an air knife coater, a curtain coater, or an extrusion coater, or a combination thereof.
[0072] Examples of the organic solvent used for forming the slurry include, but are not limited to, heptane, xylene, and toluene. Any solvent that does not chemically react with the positive electrode active material 3 and the like may be appropriately selected.
[0073] The drying and baking steps are not particularly limited as long as the organic solvent can be removed by drying the coating film, and a known drying method or baking method using a heater, etc. The coating film pressing step is also not particularly limited, and a known pressing step using a press, etc. may be used.
[0074] (2) As another method of forming the positive electrode layer 20 in the present embodiment, for example, a method of manufacturing the positive electrode layer 20 by a film forming process including a mixture preparation process, a powder lamination process, and a powder pressing process is exemplified. In the mixture preparation process, the solid electrolyte 1 and the positive electrode active material 3 in a powder state that is not slurried are prepared, and further, a binder and a conductive assistant (not shown) are prepared as necessary. The prepared materials are mixed while applying appropriate shear and pressure, to produce a positive electrode mixture in which the positive electrode active material 3 and the solid electrolyte 1 are evenly dispersed. In the powder lamination process, the obtained positive electrode mixture is evenly laminated on the positive electrode current collector 6 to obtain a laminate. In the powder pressing process, the laminate obtained in the powder lamination process is pressed.
[0075] When the positive electrode mixture in a powder state is manufactured by laminating the positive electrode mixture, there is an advantage that a drying step is not required, and the manufacturing cost is reduced. In addition, no solvent that contributes to the battery performance of the all-solid-state battery remains in the positive electrode layer 20 after film formation.
[0076] [F. Negative electrode layer deposition process] The film formation process of the negative electrode layer 30 in this embodiment (negative electrode layer formation process) is basically the same as the above [E. Positive electrode layer formation process], except that the material used is changed for the negative electrode layer 30.
[0077] The method for producing the negative electrode layer 30 may be, for example, a method in which a negative electrode mixture obtained by mixing the solid electrolyte 5, the negative electrode active material 4, and, if necessary, a binder and a conductive assistant (not shown) to form a slurry is applied onto the negative electrode current collector 7, and then dried (method (1) in [E. Positive electrode layer forming step]). Alternatively, the method for producing the negative electrode layer 30 may be, for example, a method in which a negative electrode mixture in a powder state that is not slurried is laminated onto the negative electrode current collector 7 (method (2) in [E. Positive electrode layer forming step]).
[0078] When the negative electrode mixture is manufactured by laminating powdered negative electrode mixture, there is an advantage that the drying step is not required, and the manufacturing cost is reduced. In addition, no solvent that contributes to the capacity of the all-solid-state battery remains in the negative electrode layer 30 after film formation.
[0079] [G. Solid electrolyte layer deposition process] The film formation process (solid electrolyte layer formation process) of the solid electrolyte layer 10 of the present embodiment is basically the same as the above [E. Positive electrode layer formation process] except that the material used is changed for the solid electrolyte layer 10. The solid electrolyte layer 10 of the present embodiment is formed, for example, by coating the solid electrolyte 2 in a film shape.
[0080] In the film formation process of the solid electrolyte layer 10, a solid electrolyte 2 selected from the materials listed in [B-1. Solid electrolyte] is used. Specifically, the solid electrolyte materials used for the first material 21 and the second material 22 constituting the solid electrolyte 2 are each selected from the materials listed in [B-1. Solid electrolyte]. Then, the solid electrolyte 2 and a binder, if necessary, are mixed and dispersed in an organic solvent to prepare a slurry. The obtained slurry can be prepared in the same manner as the method (1) in the above-mentioned [E. Positive electrode layer film formation process], except that the obtained slurry is applied onto the positive electrode layer 20 and / or the negative electrode layer 30 prepared above.
[0081] 2, the solid electrolyte 2 is applied in the form of a film on the positive electrode layer 20 and the negative electrode layer 30, but this is not limiting, and the solid electrolyte 2 may be applied in the form of a film on either the positive electrode layer 20 or the negative electrode layer 30. In addition, the solid electrolyte layer 10 may be produced on a substrate such as a polyethylene terephthalate (PET) film by the above-mentioned method, and the obtained solid electrolyte layer 10 may be laminated on the positive electrode layer 20 and / or the negative electrode layer 30.
[0082] Here, the solid electrolyte 2 used in forming the solid electrolyte layer 10 will be described. The solid electrolyte 2 used in forming the solid electrolyte layer 10 is formed, for example, by a stirring and kneading process in which a first material 21 and a second material 22 are stirred and mixed by a dry process. The purpose of the stirring and kneading process is to form a solid electrolyte 2 having a structure in which the surfaces of particles of the first material 21 are partially covered with the second material 22 before the solid electrolyte layer 10 is formed.
[0083] In the stirring and kneading process, the first material 21 and the second material 22 are kneaded in a dry manner by applying pressure and shearing force to form the solid electrolyte 2. Specifically, first, the first material 21 and the second material 22 are selected from the solid electrolyte materials listed in [B-1. Solid electrolyte]. As the first material 21 and the second material, for example, solid electrolyte particles are selected, respectively.
[0084] Then, the solid electrolyte particles constituting the first material 21 are defined as the first particles, and the solid electrolyte particles constituting the second material 22 are defined as the second particles, and the first particles and the second particles are mixed. In other words, the first material 21 constituted of the first particles and the second material 22 constituted of the second particles are mixed. In the present embodiment, the following description will be given assuming that the first material 21 is constituted only of the first particles and the second material 22 is constituted only of the second particles. Here, the volume ratio of the second material 22 to the total volume of the first material 21 constituted of the first particles and the second material 22 constituted of the second particles when mixing is, for example, 5% or more and 50% or less.
[0085] The average particle diameter of the first particles is, for example, 0.5 μm or more and 1.0 μm or less. In this specification, the average particle diameter is a number average particle diameter obtained by calculating the Feret diameter of the particles from an image observed by an electron microscope and calculating the number average. In addition, the ion conductivity of the first material 21 composed of the first particles is, for example, 3 mS / cm or more and 5 mS / cm or less.
[0086] In addition, the average particle diameter of the second particles is smaller than the average particle diameter of the first particles. This makes it easy to obtain the first particles partially covered with the second particles, and also makes it easy to control the mixing ratio of the first material 21 and the second material 22, so that stable battery performance can be obtained. The average particle diameter of the second particles is, for example, 0.01 μm or more and 0.1 μm or less. In addition, the ion conductivity of the second material 22 composed of the second particles is lower than the ion conductivity of the first material 21 composed of the first particles. The ion conductivity of the second material 22 composed of the second particles is, for example, 0.01 mS / cm or more and 0.3 mS / cm or less.
[0087] In addition, as a method of mixing the first particles and the second particles, for example, the second particles are added to a mixer containing the first particles and mixed and stirred, and the first particles and the second particles in the mixer are kneaded in a dry state by applying a compressive pressure and a shearing force. In this case, the method of adding the second particles may be a method of repeatedly adding the second particles little by little and mixing them by stirring.
[0088] Here, the smaller the particle diameter of the second particles, the more likely they are to aggregate, so the agglomerates of the second particles are crushed and attached to the surfaces of the first particles through the stirring and kneading process. Through the stirring and kneading process, the second particles can be partially densely packed on the surfaces of the first particles to form a state in which they are covered as a pseudo-film. The reason why this state is important will be described later.
[0089] The behavior of particles in the stirring and kneading process will be described with reference to FIG. 3. FIG. 3 is a schematic diagram showing the mixing behavior of the first particle and the second particle in the stirring and kneading process. First, as shown in FIG. 3(a), when the first particle 40 and the second particle 41 are put into a mixing and kneading device, the second particle 41 has a smaller particle diameter than the first particle 40, and therefore tends to aggregate to keep the surface energy stable, forming an aggregate 42. Here, although there is a possibility that the first particle 40 may also form an aggregate, the first particle 40 has a larger particle diameter than the second particle 41, and therefore aggregates are unlikely to occur, and therefore the first particle 40 is shown as a separate particle in FIG. 3.
[0090] Next, as shown in (b) and (c) of FIG. 3, the first particle 40 and the second particle 41 are stirred while applying a compressive pressure (pressure) and a shear force, so that the aggregates 42 of the second particle 41 are crushed by the first particle 40 and adhere to the surface of the first particle 40. Finally, as shown in (d) of FIG. 3, a coating film 43 is formed in which the second particle 41 is closely attached to the surface of the first particle 40 in a thin film shape. In this way, the second particle 41 covers a part of the surface of the first particle 40 and is in contact with the first particle 40. Depending on the hardness of the selected solid electrolyte material and the conditions of the stirring and kneading process, the second particle 41 may be plastically deformed by kneading and become a dense film. The second particle 41 may retain the particle shape when it was introduced, or may be deformed by plastic deformation to become a dense film.
[0091] By such stirring and kneading process, for example, the first particles 40 in a state in which the second particles 41 are partially coated in a film-like manner, and the solid electrolyte mixture 44 composed of a mixture of the first particles 40 and the second particles 41 remaining independently are formed. The solid electrolyte mixture 44 thus formed is used as the solid electrolyte 2 to form the solid electrolyte layer 10 by the above-mentioned method.
[0092] Thus, in the stirring and kneading process, the first material 21 composed of the first particles 40 and the second material 22 composed of the second particles 41 are kneaded in a dry manner by applying pressure and shear force to form a solid electrolyte mixture 44 to be used as the solid electrolyte 2. This stabilizes the structure in which the surfaces of the first particles 40 are coated with the second particles 41 in the solid electrolyte 2 used in the solid electrolyte layer 10.
[0093] In addition, in the solid electrolyte layer 10 formed using the solid electrolyte 2 formed in the stirring and kneading process, for example, even if the mixing ratio of the first particles 40 and the second particles 41 at any location in the thickness direction of the solid electrolyte layer 10 is calculated, the variation in the mixing ratio between locations is small. For example, when a solid electrolyte layer is formed by mixing two types of particles, large and small, in a solvent, coating and drying the mixture, the mixing ratio of the two types of particles, large and small, may change due to the influence of convection in the coating film caused by evaporation of the solvent. On the other hand, as in the present embodiment, by using the solid electrolyte 2 formed in advance by dry stirring and mixing the first particles 40 and the second particles 41 and coating the surfaces of the first particles 40 with the second particles 41, the subsequent formation of the solid electrolyte layer 10 is performed in a state in which the structure in which the surfaces of the first particles 40 are coated with the second particles 41 is easily maintained. As a result, when the solid electrolyte layer 10 is formed using the solid electrolyte 2, the local mixing ratio of the first particles 40 and the second particles 41 in the solid electrolyte layer 10 is unlikely to change. Therefore, when forming the solid electrolyte layer 10, the change in the mixing ratio of the first particles 40 and the second particles 41 in the thickness direction of the solid electrolyte layer 10 can be suppressed. For example, in a cross-sectional view when the solid electrolyte layer 10 is cut in the thickness direction, the variation in the volume ratio of the second material 22 to the total volume of the first material 21 composed of the first particles 40 and the second material 22 composed of the second particles 41 in the thickness direction of the solid electrolyte layer 10 is 10% or less. This makes it possible to obtain stable battery characteristics. Here, the variation of 10% or less means that, when the areas occupied by the first material 21 and the second material 22 are obtained by electron microscope observation and the ratio of the area of the second material 22 to the total area of the first material 21 and the second material 22 is obtained as the volume ratio, the difference in the value of the ratio at any position in the thickness direction of the solid electrolyte layer 10 is 10% or less with respect to the average value of the entire solid electrolyte layer 10.
[0094] In the above-mentioned manufacturing method, different solid electrolyte materials are selected for the first material 21 and the second material 22 to generate a difference in ion conductivity between the first material 21 and the second material 22, but the present invention is not limited to this. The manufacturing method of the all-solid-state battery 100 may include a pulverization step for forming the second material 22. Specifically, in the pulverization step, the first material 21 (specifically, the first particles 40) is pulverized in the presence of oxygen to form the second material 22 (specifically, the second particles 41). This eliminates the need to prepare two types of stable solid electrolyte materials that do not react with each other for the first material 21 and the second material 22, and therefore the second material 22 can be easily prepared. For example, a solid electrolyte material that may be oxidized, such as a sulfide-based solid electrolyte or a halide-based solid electrolyte, tends to partially deteriorate and decrease in ion conductivity when reacting with oxygen. Therefore, in the pulverization process, the first particles 40 constituting the first material 21 are pulverized under an environment of a predetermined oxygen partial pressure, so that the second particles 41 constituting the second material 22 are formed as pulverized particles while being exposed to oxygen appropriately. In this case, the oxygen content of the second material 22 is higher than the oxygen content of the first material 21. The oxygen content is, for example, the molar ratio of oxygen atoms in the solid electrolyte material. By adjusting the oxygen partial pressure when pulverizing the first material 21 and adjusting the oxygen content of the second material 22, it is possible to adjust the ionic conductivity of the second material 22.
[0095] The second material 22 having a higher oxygen content than the first material 21 may be particles formed by pulverizing a solid electrolyte material other than the first material 21 under an oxygen atmosphere. In this case, the ionic conductivity of the second material 22 can be easily adjusted.
[0096] [H. Lamination and pressing process] In the lamination process and the pressing process, the positive electrode layer 20 formed on the positive electrode current collector 6, the negative electrode layer 30 formed on the negative electrode current collector 7, and the solid electrolyte layer 10 obtained by each film formation process are laminated (lamination process) so that the solid electrolyte layer 10 is disposed between the positive electrode layer 20 and the negative electrode layer 30, and then the positive electrode current collector 6 and the negative electrode current collector 7 are pressed from the outside (pressing process) to obtain the all-solid-state battery 100.
[0097] The purpose of pressing is to increase the density of the positive electrode layer 20, the negative electrode layer 30, and the solid electrolyte layer 10. By increasing the density, the lithium ion conductivity and the electronic conductivity can be improved in the positive electrode layer 20, the negative electrode layer 30, and the solid electrolyte layer 10, and an all-solid-state battery 100 having good battery characteristics can be obtained.
[0098] <Example> Examples of the solid electrolyte layer of the all-solid-state battery according to the present embodiment will be described below, but the present embodiment is not limited to these examples. Unless otherwise specified, each example was performed in a glove box or a dry room where the dew point was controlled to be −45° C. or lower.
[0099] Specifically, in order to evaluate the effect of the solid electrolyte layer of the all-solid-state battery according to the present embodiment, a short circuit test due to simple dendrite generation was carried out. FIG. 4 is a schematic diagram showing a cross section of an evaluation sample 48 used in Comparative Example 1 and Example 1. As shown in FIG. 4, the evaluation sample 48 includes a first electrode 46, a second electrode 47 arranged opposite to the first electrode 46, and a solid electrolyte layer 45 located between the first electrode 46 and the second electrode 47.
[0100] (1) Preparation of Evaluation Sample 48 in Comparative Example 1 First, only the first particles 40 made of a sulfide-based solid electrolyte as the solid electrolyte of the solid electrolyte layer 45 were laminated so as to be sandwiched between a first electrode 46 made of metal Li and a second electrode 47 made of Cu. Next, the laminated structure was pressed from above and below in the lamination direction with an adjusted pressure of 200 to 300 MPa. In this way, an evaluation sample 48 in Comparative Example 1 was produced, in which the solid electrolyte layer 45 formed by pressing the first particles 40 was sandwiched between the first electrode 46 and the second electrode 47.
[0101] (2) Production of Evaluation Sample 48 in Example 1 The evaluation sample 48 in Example 1 was produced in the same manner as the evaluation sample 48 in Comparative Example 1, except that a solid electrolyte formed by a stirring and kneading process using the first particle 40 made of the same sulfide-based solid electrolyte as in Comparative Example 1 and the second particle 41 made of a solid electrolyte material in which the oxygen content of the sulfide-based solid electrolyte is higher than that of the first particle 40 by the above-mentioned method was used as the solid electrolyte of the solid electrolyte layer 45. That is, the solid electrolyte layer 45 of the evaluation sample 48 in Example 1 has the same configuration as the above-mentioned solid electrolyte layer 10. At this time, the volume ratio of the second particle 41 to the total volume of the first particle 40 and the second particle 41 was 15 to 25%.
[0102] (3) Short circuit test A positive terminal was connected to the first electrode 46 of the obtained evaluation sample 48, and a negative terminal was connected to the second electrode 47, and a current of 0.1 to 0.4 mA was continuously applied to the evaluation sample 48 as a predetermined constant current assuming a current value flowing during charging and discharging of an all-solid-state battery. If the constant current is continuously applied, a short circuit occurs due to the generation of dendrites, causing a sudden drop in voltage, so the time required from the start of application of the constant current until a short circuit (in other words, a sudden drop in voltage) was measured. The measurement results are shown in Table 1. In Table 1, the "ratio of time required until short circuit occurs" is a ratio obtained by comparing the time required until short circuit occurs between the evaluation sample 48 in Comparative Example 1 and the evaluation sample 48 in Example 1, assuming the time in Comparative Example 1 to be 1.
[0103] [Table 1]
[0104] As shown in Table 1, it was confirmed that evaluation sample 48 in Example 1 did not short circuit even after 20 times the time required for evaluation sample 48 in Comparative Example 1 to short circuit, and the time required for short circuit was increased. This is considered to be due to the effect that second particles 41 having lower ionic conductivity than first particles 40 are appropriately dispersed and present at the particle interfaces formed between first particles 40, which are solid electrolyte particles, in solid electrolyte layer 45. The mechanism that may be the reason for this result will be described with reference to Figs. 5 and 6.
[0105] Fig. 5 is a schematic diagram for explaining the state of dendrite generation in evaluation sample 48 in Comparative Example 1. Fig. 6 is a schematic diagram for explaining the state of dendrite generation in evaluation sample 48 in Example 1. Fig. 5 shows a cross section of evaluation sample 48 in Comparative Example 1, and Fig. 6 shows a cross section of evaluation sample 48 in Example 1. Figs. 5 and 6 show a schematic diagram of the state of dendrite generation inside solid electrolyte layer 45 sandwiched between first electrode 46 and second electrode 47.
[0106] By applying a constant current to the evaluation sample 48, Li ions 50, which are ionized metal Li of the first electrode 46, are conducted within the first particles 40 constituting the solid electrolyte layer 45. When the Li ions 50 conducted within the first particles 40 reach the second electrode 47, they are precipitated as metal Li on the surface of the second electrode 47. By continuously applying a constant current for a long period of time, the metal Li precipitated on the surface of the second electrode 47 grows as dendrites 51 along the particle interfaces of the first particles 40 formed by the plastic deformation of the particles of the first particles 40 and along the surfaces of the first particles 40. At that time, in the evaluation sample 48 in Comparative Example 1 shown in FIG. 5, the Li ions 50 conducted within the first particles 40 are concentrated and conducted to the metal Li present at the shortest distance, that is, the part of the dendrite 51 close to the first electrode 46, and the metal Li is precipitated at the part of the dendrite 51 close to the first electrode 46, so that the dendrite 51 grows further. As a result, dendrites 51 tend to grow from second electrode 47 toward first electrode 46 over the shortest distance within solid electrolyte layer 45. When grown dendrites 51 reach first electrode 46, a short circuit occurs.
[0107] In contrast, in the evaluation sample 48 in Example 1 shown in FIG. 6, a solid electrolyte material (second particle 41 in the figure) having a lower ion conductivity than the first particle 40 is present on the surface of the first particle 40. As a result, the second particle 41 becomes a resistance component in ion conduction, and promotes the Li ion 50 to bypass the conductive path, which is considered to have the effect of suppressing the dendrite 51 from growing in the shortest distance. In other words, the dendrite 51 grows along the surface of the first particle 40 while bypassing the portion where the second particle 41 covers the first particle 40. For example, the dendrite 51 grows by branching. As a result, in the evaluation sample 48 in Example 1, it is considered that the grown dendrite 51 is difficult to reach the first electrode 46, and the time required for a short circuit is prolonged. Therefore, the occurrence of a short circuit can be suppressed even in the all-solid-state battery 100 including the solid electrolyte layer 10 having the same configuration as the solid electrolyte layer 45 of the evaluation sample 48 in Example 1.
[0108] The configuration of the solid electrolyte layer 10 in the all-solid-state battery 100 for more efficiently obtaining the above-mentioned effect of suppressing short circuits will be described below.
[0109] The coverage of the second material 22 (specifically, the second particles 41 constituting the second material 22) on the surface of the first particle 40 is, for example, 5% or more and 62% or less. When the coverage is 5% or more, the above-mentioned effect of diverting the growth of dendrites and suppressing the occurrence of a short circuit is easily obtained. When the coverage is 62% or less, the resistance component in the ion conduction of the solid electrolyte layer 10 is unlikely to increase, and the efficiency as a battery is unlikely to decrease. From the viewpoint of achieving both the suppression of a short circuit and the efficiency as a battery, the coverage may be 10% or more and 50% or less. The coverage is an average coverage of the first particle 40, and is measured, for example, by observing an electron microscope photograph of the solid electrolyte layer 10.
[0110] Furthermore, at the particle interface formed between the first particles 40, for example, there is an interface where the first particles 40 are in contact with each other. As a result, the second particles 41 are not present over the entire surface of the particle interface, and therefore, the resistance component in the ion conduction of the solid electrolyte layer 10 can be reduced.
[0111] Furthermore, the ratio of the average particle diameter of the second particles 41 to the average particle diameter of the first particles 40 is, for example, 1% or more and 20% or less. When the ratio is 1% or more, the second particles 41 are less likely to aggregate with each other, and the surfaces of the first particles 40 are more likely to be covered by the second particles 41. When the ratio is 20% or less, the number of the second particles 41 is ensured, and the surfaces of the first particles 40 are more likely to be covered by the second particles 41. From the viewpoint of making it even easier for the surfaces of the first particles 40 to be covered by the second particles 41, the ratio may be 5% or more and 20% or less.
[0112] Here, the state in which the second particle 41 covers the first particle 40 will be described with reference to FIG. 7A and FIG. 7B. FIG. 7A is a perspective view that shows a schematic diagram of the state in which the second particle 41 covers the first particle 40. FIG. 7B is a cross-sectional view of the first particle 40 and the second particle 41 shown in FIG. 7A cut along the plane VIIb shown by the dashed line. FIG. 7A shows a state in which the second particle 41 covers the surface of one of the first particles 40 as a coating film 43 and is sandwiched between other particles of the first particle 40. Here, in the coating structure of the second material 22, which is the coating film 43 of the second particle 41 that covers the surface of the first particle 40, the maximum value of the length in the direction of the distance between the first particles 40 (in other words, the normal direction of the particle surface of the first particle 40) at the interface 52 formed between the first particles 40 is defined as the coating thickness L1, and the maximum value of the length in the direction along the interface 52 (in other words, the direction along the particle surface of the first particle 40) is defined as the coating length L2. In at least one of the coating structures (here, coating film 43) of second particle 41 that coats first particle 40, coating length L2 is, for example, 10 times or more the coating thickness L1. This makes it easier to obtain the effect of diverting the growth of dendrites described above while suppressing an increase in the resistance component in ion conduction in the thickness direction of coating film 43.
[0113] Moreover, the volume ratio of the first material 21 composed of the first particles 40 to the second material 22 composed of the second particles 41 is, for example, 5% or more and 50% or less. When the volume ratio is 5% or more, the effect of bypassing the growth of dendrites described above is easily obtained. When the volume ratio is 50% or less, the resistance component in the ion conduction of the solid electrolyte layer 10 is unlikely to increase, and the efficiency as a battery is unlikely to decrease. From the viewpoint of achieving both suppression of short circuits and efficiency as a battery, the volume ratio may be 10% or more and 30% or less.
[0114] Furthermore, the ratio of the ionic conductivity of the second material 22 formed of the second particles 41 to the ionic conductivity of the first material 21 formed of the first particles 40 is, for example, 0.2% or more and 10% or less. When the ratio is 10% or less, the effect of bypassing the growth of dendrites described above is easily obtained. When the ratio is 0.2% or more, the resistance component in the ionic conduction of the solid electrolyte layer 10 is unlikely to increase, and the efficiency as a battery is unlikely to decrease.
[0115] Although the all-solid-state battery according to the present disclosure has been described based on the embodiments, the present disclosure is not limited to these embodiments. As long as it does not deviate from the gist of the present disclosure, various modifications conceivable by a person skilled in the art to the embodiments and other forms constructed by combining some of the components in the embodiments are also included in the scope of the present disclosure.
[0116] For example, in the above embodiment, the ions that conduct through the solid electrolyte layer 10 are lithium ions, but this is not limiting. The ions that conduct through the solid electrolyte layer 10 may be ions other than lithium ions, such as sodium ions, magnesium ions, potassium ions, calcium ions, or copper ions. [Industrial Applicability]
[0117] The all-solid-state battery according to the present disclosure is expected to be applied to a variety of batteries, such as power sources for portable electronic devices and automotive batteries. [Explanation of symbols]
[0118] 1, 2, 5 Solid electrolyte 3 Cathode active material 4 Negative electrode active material 6 Positive electrode current collector 7 Negative electrode current collector 10, 45 solid electrolyte layer 20 Positive electrode layer 21 First material 22 Second material 30 Negative electrode layer 40 1st particle 41 2nd particle 42 Aggregates 43 Coating film 44 Solid electrolyte mixture 46 1st electrode 47 Second electrode 48 Evaluation Samples 50 Li-ion 51 Dendrite 52 Interface 100 solid state battery
Claims
1. A positive electrode current collector; a positive electrode layer including a positive electrode active material and a first solid electrolyte; a solid electrolyte layer including a third solid electrolyte; a negative electrode layer including a negative electrode active material and a second solid electrolyte; a negative electrode current collector and a negative electrode current collector laminated in this order, the third solid electrolyte is composed of a first material and a second material having an ionic conductivity lower than that of the first material, the first material is composed of first particles; At least a portion of a surface of the first particle is coated with the second material; The oxygen content of the second material is higher than the oxygen content of the first material. All-solid-state battery.
2. A coverage rate of the surface of the first particle with the second material is 5% or more and 62% or less. The all-solid-state battery according to claim 1 .
3. The second material is composed of second particles having an average particle size smaller than that of the first particles. The all-solid-state battery according to claim 1 or 2.
4. A ratio of an average particle size of the second particles to an average particle size of the first particles is 1% or more and 20% or less. The all-solid-state battery according to claim 3 .
5. In the coating structure of the second material that coats the first particles, the coating length is 10 times or more as large as the coating thickness. The all-solid-state battery according to any one of claims 1 to 4.
6. A volume ratio of the second material to a total volume of the first material and the second material is 5% or more and 50% or less. The all-solid-state battery according to any one of claims 1 to 5.
7. In a cross-sectional view of the solid electrolyte layer, a variation in a volume ratio of the second material to a total volume of the first material and the second material in a thickness direction of the solid electrolyte layer is 10% or less. The all-solid-state battery according to any one of claims 1 to 6.
8. The ratio of the ionic conductivity of the second material to the ionic conductivity of the first material is 0.2% or more and 10% or less. The all-solid-state battery according to any one of claims 1 to 7.
9. The method for producing an all-solid-state battery according to any one of claims 1 to 8, a stirring and kneading step of forming the third solid electrolyte by applying a pressure force and a shear force to the first material and the second material in a dry state before forming the solid electrolyte layer; Prior to the stirring and kneading step, the first material is pulverized in the presence of oxygen to form the second material and a grinding step to form How solid-state batteries are manufactured.
10. A method for producing an all-solid-state battery, comprising: The all-solid-state battery comprises: A positive electrode current collector; a positive electrode layer including a positive electrode active material and a first solid electrolyte; a solid electrolyte layer including a third solid electrolyte; a negative electrode layer including a negative electrode active material and a second solid electrolyte; a negative electrode current collector and a negative electrode current collector laminated in this order, the third solid electrolyte is composed of a first material and a second material having an ionic conductivity lower than that of the first material, the first material is composed of first particles; At least a portion of a surface of the first particle is coated with the second material; The manufacturing method includes: a stirring and kneading step of forming the third solid electrolyte by applying a pressure force and a shear force to the first material and the second material in a dry state before forming the solid electrolyte layer; Prior to the stirring and kneading step, the first material is pulverized in the presence of oxygen to form the second material The method further comprises the step of grinding to form How solid-state batteries are manufactured.
Citation Information
Patent Citations
All solid battery
JP2013157084A
Composite electrolyte, secondary battery, battery pack and vehicle
JP2018160445A
Sulfide solid electrolyte material and battery using the same
JP2019050182A
Lithium ion conductor, solid electrolyte layer, electrode, battery and electronic device
WO2016157751A1
Solid electrolyte and battery using same
WO2020100465A1